(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
This paper estimated cypermethrin residues 32% and abamectin residues 1.8% on three different summer vegetables (eggplant, zucchini, pepper) grown in greenhouses during winter. Health risk indices (DIR, HIR Health Risk Index) were measured for vegetables consumers in the southern regions (Ubari, Wadi Alshatti, Tragen, Wadi Utba). The results revealed that the concentrations of cypermethrin residues exceeded the permissible limits in studied vegetables except the zucchini, and the highest concentrations were detected in eggplant (4.71 μg/g) followed by pepper (1.15 μg/g). The residues of abamectin also exceeded the permissible limits in all vegetables, the highest was eggplant (1.65 μg/g), followed by pepper (1.22 μg/g), finally zucchini (0.69 μg/g). Data also showed that the highest daily consumption rate for cypermethrin and abamectin was in the Ubari region, especially in eggplant fruits, i.e., 0.1325 and 0.0075 g/day, respectively. With regard to the risk indicator for the presence of pesticides in question in studied vegetables, the approach of the health risk index is dangerous (0.5) in the Wadi-Alshati area and very dangerous (0.6) in the Ubari region due to zucchini consumption accordance to FAO standards (1). Lies in the accumulation of these compounds within the human body and lack in awareness of farmers and greenhouse labor is an important in prohibition period, which is considered an opportunity to break, fly or dispose of a large part of these residues before they reach consumers. Consumers should be alerted to this and to reduce the consumption of greenhouse products to prevent the circulation and use of these dangerous pesticides.